Factors associated with knowledge, attitude and practice of e-cigarette among adult population in KOSPEN areas of Kuching district, Sarawak, Malaysia - Hafiz, Ahmad; Rahman, M. Mizanur; Jantan, Zulkifli (International Journal Of Community Medicine And Public Health, 2019)
Background: Smoking electronic cigarette is a current world phenomenon, however, the vaping community had ignorant about its health effects. Considering this view, this study was conducted to determine the level of knowledge and attitude toward e-cigarette and factors associated with it. Methods: This cross-sectional study was conducted among adults in the KOSPEN locality in Kuching district. Six out of the 64 KOSPEN localities had been chosen randomly as study locations. Systematic random sampling with replacement method was used to select the respondent. A total of 354 adults were interviewed by face to face interview using adapted and validated questionnaire. The data entry and analysis were done by IBM SPSS Version 22.0. A p<0.05 was considered as statistically significant. Results: Data revealed that 66% of the respondents admitted that they heard about e-cigarette. Among them 54.3% of the respondent had good knowledge about e-cigarette. However, more than half (52.8%) do not support the use of e-cigarette. Bi-variate analysis revealed that male gender and attitude towards supporting e-cigarette was significantly associated with practice of e-cigarette (p<0.05). However, for the conventional practice of smoking, age, gender, marital status, level of education and occupation found to be significantly associated with practice of conventional smoking. Conclusions: Though the study did not depict the national scenarios of e-smoking and conventional cigarette smoking as well, but the factors identified in this study appeared to be policy options for the programme managers, health administration, and health educators designing the preventive programmes against e-smoking and conventional smoking.